Anti-hyperuricemia effect of hesperetin is mediated by inhibiting the activity of xanthine oxidase and promoting excretion of uric acid - An, Meng-Fei; Shen, Chang; Zhang, Shao-Shi; Wang, Ming-Yue; Sun, Ze-Rui; Fan, Mao-Si; Zhang, Li-Juan; Zhao, Yun-Li; Sheng, Jun; Wang, Xuan-Jun (Frontiers in Pharmacology, 2023)
Hesperetin is a natural flavonoid with many biological activities. In view of hyperuricemia treatment, the effects of hesperetin in vivo and in vitro, and the underlying mechanisms, were explored. Hyperuricemia models induced by yeast extract (YE) or potassium oxonate (PO) in mice were created, as were models based on hypoxanthine and xanthine oxidase (XOD) in L-O2 cells and sodium urate in HEK293T cells. Serum level of uric acid (UA), creatinine (CRE), and urea nitrogen (BUN) were reduced significantly after hesperetin treatment in vivo. Hesperetin provided hepatoprotective effects and inhibited xanthine oxidase activity markedly, altered the level of malondialdehyde (MDA), glutathione peroxidase (GSH-PX) and catalase (CAT), downregulated the XOD protein expression, toll-like receptor (TLR)4, nucleotide binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, interleukin-18 (IL-18), upregulated forkhead box O3a (FOXO3a), manganese superoxide dismutase (MnSOD) in a uric acid-synthesis model in mice. Protein expression of organic anion transporter 1 (OAT1), OAT3, organic cationic transporter 1 (OCT1), and OCT2 was upregulated by hesperetin intervention in a uric acid excretion model in mice. Our results proposal that hesperetin exerts a uric acid-lowering effect through inhibiting xanthine oxidase activity and protein expression, intervening in the TLR4-NLRP3 inflammasome signaling pathway, and up-regulating expression of FOXO3a, MnSOD, OAT1, OAT3, OCT1, and OCT2 proteins. Thus, hesperetin could be a promising therapeutic agent against hyperuricemia.